Factors influencing PNG format image size in case of linear geometrical entities. (10th April 2015) - Horák, Jiří; Růžička, Jan; Szturcová, Daniela; Ardielli, Jiří
The research is focused on the study of the impact of the number and the pattern of geometrical entities and colour models in map like drawings upon the file size of PNG format. The extended sample set of PNG images was generated by web map services of 15 European servers. Original images were transformed into different colour models of PNG (RGBA, RGB, Palette, interlaced, non-interlaced) and the differences of file sizes were analysed. Main influencing factors are the colour model, image density, size of lines, anti-aliasing effect and interlacing. The complexity of map drawings can be approximated by the ratio of foreground pixels in an image. In order to minimise files sizes it is recommended to transform images into appropriate palette models, to avoid anti-aliasing changes of transparency and to prefer wide lines.